Virtues, Work Satisfactions and Psychological Well-Being among Nurses in Turkish Hospitals - Ronald J Burke; Mustafa Koyuncu; Ufuk Durna; Recep Cicek; Lisa Fiksenbaum (Archives of Nursing Practice and Care - Peertechz Publications, 2016)
This exploratory study examined the relationship between virtues and indicators of work satisfaction and engagement, perceptions of hospital functioning and quality of nursing care, and psychological well-being of nursing staff. Working in Turkish hospitals. A virtue is any psychological process that enables a person to benefit himself or herself and others. Two virtues were considered: optimism and proactive behaviors. This emphasis was consistent with emerging trends in both psychology and organizational studies, termed positive psychology or positive organizational scholarship respectively, to focus on strengths and  excellence rather than weakness and pathology. Data were collected from 224 staff nurses in Ankara Turkey using anonymously completed questionnaires, a 37% response rate. Hierarchical regression analyses, controlling for both personal demographic and work situation characteristics, indicated that virtues accounted for significant increments in explained variance on most outcome measures. Optimism emerged as a particularly consistent predictor of these. Explanations for the association of virtues with favorable outcomes are offered along with potentially practical implications. Future research should  employ longitudinal designs to experimentally examine the influence of virtues on work outcomes and well-being over time and the effects of initiatives to increase levels of virtuous behavior and attitudes.